2015
DOI: 10.1007/s00332-015-9268-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex Oscillations in the Delayed FitzHugh–Nagumo Equation

Abstract: Motivated by the dynamics of neuronal responses, we analyze the dynamics of the FitzHugh-Nagumo slow-fast system with delayed self-coupling. This system provides a canonical example of a canard explosion for sufficiently small delays. Beyond this regime, delays significantly enrich the dynamics, leading to mixed-mode oscillations, bursting and chaos. These behaviors emerge from a delay-induced subcritical Bogdanov-Takens instability arising at the fold points of the S-shaped critical manifold. Underlying the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The FHN neuron model (for biophysical details, see [55]) has been extensively used to investigate many complex dynamical behaviors occurring in neuroscience [56][57][58][59][60]. For our investigation of SISR, we consider the following version of the FHN neuron model written on the slow timescale τ as…”
Section: Model Equationmentioning
confidence: 99%
“…The FHN neuron model (for biophysical details, see [55]) has been extensively used to investigate many complex dynamical behaviors occurring in neuroscience [56][57][58][59][60]. For our investigation of SISR, we consider the following version of the FHN neuron model written on the slow timescale τ as…”
Section: Model Equationmentioning
confidence: 99%
“…In Ref. [31], the authors investigated Eqs. (1) with c < 0 and determined the possible routes to chaos [32].…”
Section: Introductionmentioning
confidence: 99%
“…We also show the existence of one, two, or three different modes of spiking as a result of pitchfork cycle and torus (Neimark-Sacker) bifurcations. We want to emphasize that, by BendixsonDulac theorem, it can be seen that the single neuron of the FHN model does not admit periodic solutions for the ranges chosen in our paper, unlike the system in [28] whose dynamics, in the absence of delays, is characterized by a canard explosion and relaxation oscillations. Thus the periodic solutions are due to coupling of the neurons, or time delay.…”
Section: Introductionmentioning
confidence: 94%
“…There are many technological and biological systems which exhibit such behavior. Some examples of delayed systems are coupled lasers [26], high-speed milling, population dynamics, epidemiology [27], and gene expression, Krupa and Touboul [28] investigated a self-coupled delayed FHN system to understand the effect of introducing delays in a system whose dynamics, in the absence of delays, is characterized by a canard explosion and relaxation oscillations. They have shown that delays significantly enrich the dynamics, leading to mixed-mode oscillations, bursting, canard and chaos.…”
Section: Introductionmentioning
confidence: 99%